Slope does not affect autonomous recorder detection shape: considerations for acoustic monitoring in forested landscapes. Issue 3 (4th May 2022) - Shaw, Taylor; Müller, Sandra; Scherer-Lorenzen, Michael
ABSTRACT: To date, there are no published guidelines on how to optimally install recorders on sloped terrain, although slope could potentially affect a recorder's detection space. This study experimentally investigated the effect of microphone orientation in relation to slope of recorders from two cost classes. We installed four recorders at each plot centre (n = 16), oriented either parallel or perpendicular to the slope. We played standard tones of 1–11 kHz at distances of 10, 20, 40 and 80 m from the recorders. Our two response variables were the presence/absence of each tone (coarse spatial scale) and predicted sound extinction distance (fine spatial scale), which were tested for effects of microphone orientation and sound source direction (SSD). We observed a significant effect of microphone orientation on extinction distance when recorders were perpendicular to the slope at the finer spatial scale as an interaction with SSD, indicating that microphones are biased towards the direction they face. Despite the advertised directionality of most recorder microphones, detection space is not circular. This trend was observed across all frequencies, for both high- and low-cost recorders. Microphone orientation in relation to slope is not an important methodological consideration, instead dominant factors such as frequency and prevailing wind direction drive detection space shape.